Nostalgia and heritage in Korsten, Port Elizabeth, 1956 to 1990 - Wintermeyer, Bryan (Conservation of the Built Environment, 2015)
This study centres on interdisciplinary notions of 'place’ (and its structures), the attachment to place, their ordinary and everyday potential heritage resources and the value of nostalgia as a method for engaging with these marginal heritages. The case is a set of values of a group of past users of a series of entertainment structures in Korsten, Port Elizabeth, from 1956 to 1990. Their everyday experience of living in Korsten, together with the trauma of displacement (as a consequence of forced removals) and the nostalgia associated with the joy of an 'era of entertainment’ they experienced as young adults in new structures such as grand cinemas and dance halls, is central to addressing the argument of this study. Three themes were explored through interviews with eight people. These were: the user experience, responses to nostalgia and the nature of the potential heritage resource. The interviews were initiated by open-ended questions that allowed for diversion and storytelling.